Co2+ substituted La2CuO4/LaCoO3 perovskite nanocomposites: synthesis, properties and heterogeneous catalytic performance. (16th October 2018) - Sukumar, M.; Kennedy, L. John; Vijaya, J. Judith; Al-Najar, B.; Bououdina, M.
Abstract : Cobalt substituted La2 CuO4 /LaCoO3 perovskite nanocomposites were prepared using a microwave combustion method. Abstract : Cobalt substituted La2 CuO4 /LaCoO3 perovskite nanocomposites were prepared using a microwave combustion method. X-ray diffraction analysis showed that Co 2+ substitution in La2 CuO4 induced the formation of a secondary LaCoO3 phase with rhombohedral structure along with the existing orthorhombic (La2 CuO4 ) structure. The orthorhombic/rhombohedral structured nanocomposites possessed an average crystallite size in the range of 36–46 nm and 21–49 nm, respectively. The Rietveld analysis confirmed the formation of these two phases. The appearance of FT-IR bands around 682 and 512 cm −1 was correlated to the orthorhombic stretching modes while the bands around 580 and 445 cm −1 were associated with the rhombohedral stretching modes thereby confirming the two-phase perovskite system. An optical study revealed two linear regions depicting two band gaps related to the La2 CuO4 and LaCoO3 phases. The band gap was found to increase with an increase in the Co 2+ doping fraction. Morphological observations using scanning electron microscopy showed intragranular pores and fused grains with distinct grain boundaries. The change in the magnetic properties was associated most probably with the exchange of the A and B sites within the La2 CuO4 host lattice because of Co 2+ doping, as well as the important phase composition of La2 CuO4 /LaCoO3 obtained from the ferromagnetic-to-paramagnetic transition. The BET surface area of the pure and doped nanocomposites was found to vary considerably within the range of 12.2–43.7 m 2 g −1 . The as-fabricated La2 CuO4 /LaCoO3 perovskite nanocomposites were evaluated for the conversion of glycerol to formic acid in a liquid phase batch reactor under atmospheric conditions. This La 3+ based nanocomposite behaves as an efficient bifunctional catalyst with high conversion efficiency and selectivity around 96.5% and 95.1%, respectively.